Poverty alleviation on a sustainable basis in the Islamic framework - Akhtar, Muhammad Ramzan (The Pakistan development review, 2000)
The Islamic approach for poverty alleviation is based on the premise that poverty is a historical phenomenon bearing multiple dimensions and causal roots. It is defined as a situation of non-satisfaction of material and socio-political ingredients that provide well-being. The absence of these ingredients causes human deprivation and diminution in the required level of human well-being consistent with the lofty status of man. A satisfactory solution of the poverty problem needs implementing a comprehensive policy package that realises accelerated growth favouring poor people. Political and administrative reforms enable these peoples to participate and mould the decision-making processes in their favour. The Islamic social security system, by providing adequate safeguards against risky conditions, enables poor people to live a relatively stable and peaceful life. (Pak Dev Rev/DÜI)